Prêcher contre la mécréance. Le problème de l’hétérodoxie dans les sermons de Jean Gerson - Christophe Grellard (Etudes Epistémè)
This article explores the duties of the preacher according to Jean Gerson: the duties of teaching and strengthening the faith can be used to point out the discursive forms deployed against heterodoxy (heresy, schism, blasphemy, etc.) in Gerson’s preaching. The preacher must then prevent the birth of bad ideas in the faithful’s mind through polemic. Gerson thus limits the scope of polemic by fighting his adversaries in an abstract and allegorical way, and by subordinating any dispute to the authority of faith.